Epidemiology of injury and illness in North American professional men`s soccer: Comparing COVID-19 lockdown with previous seasons - Hardin, S.; Silverman, R.; Brophy, R.; Putukian, M.; Silvers-Granelli, H. (Sports Health: A Multidisciplinary Approach, 2024)
Background: After COVID-19 lockdown, studies across Europe and Asia examined its effect on professional soccer injury rates and severity; however, COVID-19 lockdown influence on injuries in United States men`s professional soccer has not been evaluated.